Несгибаемый: сборник / Константин Калбазов - Калбазов Константин Георгиевич (БФ-коллекция, 2022)
Экземпляры: ф.15 (20230418) / Инвентарный номер: 63386 / Цена: / Сис.шифр: 84(2Рос=411.2)6-4 / Авт.знак: К 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-445.1